Preparation method of underwater in-situ curing bonding material based on iron nanoparticles and application thereof
Patent Information
- Application Number
- CN202610970402.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-01
- Publication Date
- 2026-10-20
AI Technical Summary
然而,这种依赖对外部能量固化的技术不仅增加了实际操作的复杂性,而且在特定环境下(如深海作业或低温环境)难以实施,限制了水下黏附材料的应用范围
1、本发明以胺基封端的聚二甲基硅氧烷、支化结构多官能团丙烯酸酯、柔性双丙烯酸酯、多巴胺盐酸盐和苄胺盐酸盐为反应组分,经迈克尔加成反应形成超支化黏附材料。该材料同时含有疏水链段和多巴胺基团,疏水链段在水下可削弱水分子对胶黏层的干扰,多巴胺基团可参与基底界面作用,适合用于水下原位黏结。
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of underwater in-situ solidification adhesive materials technology, and more specifically, to a method for preparing underwater in-situ solidification adhesive materials based on iron nanoparticles and its application. Background Technology
[0002] Underwater adhesives offer a wide range of applications, including direct underwater bonding, reinforcement, repair, and sealing. For example, they can be used to seal data sensors, hydraulic and pneumatic systems, and to cure and urgently repair mechanical joints and moving parts, ensuring stable operation and effective data transmission in underwater environments over extended periods.
[0003] Currently, epoxy resins and polyurethane adhesives require curing in a non-wet state, making direct underwater operation difficult. This is mainly because water molecules not only penetrate into the adhesive through Brownian motion, causing swelling, hydrolysis, and plasticization of the polymer network, but also react with the hydrophilic groups in the adhesive, severely damaging the adhesive's cohesive energy.
[0004] Currently, the cohesive energy of adhesive materials is increased by introducing external energy sources (such as temperature, ultraviolet light irradiation, and the addition of oxidants) to trigger the underwater curing process, thereby raising the adhesive strength from several kilopascals to several megapascals. Existing technology (Chinese patent CN113493665A) discloses a method for preparing a palm oil-based underwater adhesive. This patent prepares the palm oil-based underwater adhesive by blending synthesized palm oil fatty acid ethyl acrylamide with isobornyl acrylate and then using ultraviolet light curing technology. However, this technology, which relies on external energy for curing, not only increases the complexity of practical operation but is also difficult to implement in specific environments (such as deep-sea operations or low-temperature environments), limiting the application range of underwater adhesive materials.
[0005] Therefore, we propose a method for preparing underwater in-situ solidified adhesive materials based on iron nanoparticles and its application to solve the above problems. Summary of the Invention
[0006] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a method for preparing underwater in-situ solidified adhesive materials based on iron nanoparticle regulation and its application, so as to solve the problems mentioned in the background art.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing an underwater in-situ solidification bonding material based on iron nanoparticle regulation, comprising the following steps: Amine-terminated polydimethylsiloxane, branched polyfunctional acrylate, flexible diacrylate, dopamine hydrochloride and benzylamine hydrochloride were mixed in an organic solvent and subjected to Michael addition reaction under alkaline conditions. The reaction product was then precipitated to obtain a hyperbranched adhesive material. The hyperbranched adhesive material is dissolved in an organic solvent to obtain an adhesive solution; Iron nanoparticles are dispersed in the adhesive solution to obtain an adhesive solution containing iron nanoparticles, wherein the iron nanoparticles are used to form coordination with dopamine hydroxyl groups in the hyperbranched adhesive material. An adhesive solution containing iron nanoparticles is applied to the surface of a first substrate to form an adhesive layer. The first substrate is placed underwater, and a second substrate is placed underwater to cover the adhesive layer. Pressure is applied to the joint end face, and underwater in-situ curing is performed to obtain an underwater bonded joint.
[0008] In a preferred embodiment, the amino-terminated polydimethylsiloxane is first dissolved in N,N-dimethylformamide, and the branched multifunctional acrylate, flexible diacrylate, dopamine hydrochloride and benzylamine hydrochloride are first dissolved in dimethyl sulfoxide. The two solutions are then mixed to carry out the Michael addition reaction.
[0009] In a preferred embodiment, the branched multifunctional acrylate includes one or more of pentaerythritol triacrylate and polydipentaerythritol hexaacrylate; the flexible diacrylate includes one or more of polyethylene glycol diacrylate, 1,10-bisacryloyloxydecane, and 1,4-butanediol diacrylate.
[0010] In a preferred embodiment, the Michael addition reaction is carried out under alkaline conditions, at a temperature of 70°C to 90°C, for a reaction time of 4 to 7 hours.
[0011] In a preferred embodiment, the molar ratio of double bonds to amino groups in the monomers participating in the Michael addition reaction is (1:0.5) to (1.5:0.5).
[0012] In a preferred embodiment, the reaction product is precipitated with methyl tert-butyl ether to obtain the hyperbranched adhesive material; the mass ratio of the hyperbranched adhesive material to the organic solvent used for dissolution is (1:0.5) to (1:3).
[0013] In a preferred embodiment, the organic solvent in the adhesive solution includes one or more of methanol, dimethyl sulfoxide, dichloromethane, acetone, and N,N-methylpropionamide; the mass of the iron nanoparticles is 0.5% to 2% of the mass of the adhesive solution.
[0014] In a preferred embodiment, the adhesive solution containing iron nanoparticles is applied to the surface of the first substrate by coating, dipping, spraying or immersion; after the second substrate covers the adhesive layer, it is pressed for 3 min to 10 min and then cured underwater in situ for 12 h to 48 h under pressure at the joint end face.
[0015] In a preferred embodiment, the underwater in-situ curing adhesive material prepared according to the preparation method is used in underwater substrate bonding, reinforcement, repair or sealing.
[0016] The technical effects and advantages of this invention are as follows: 1. This invention uses amino-terminated polydimethylsiloxane, branched multifunctional acrylate, flexible diacrylate, dopamine hydrochloride, and benzylamine hydrochloride as reactants to form a hyperbranched adhesive material via a Michael addition reaction. This material contains both hydrophobic segments and dopamine groups. The hydrophobic segments can reduce the interference of water molecules on the adhesive layer underwater, while the dopamine groups can participate in substrate-interfacial interactions, making it suitable for underwater in-situ bonding.
[0017] 2. This invention introduces iron nanoparticles into the adhesive solution. The iron nanoparticles can form coordination with the dopamine hydroxyl groups in the hyperbranched adhesive material, thereby regulating the cohesive state of the adhesive material. This avoids relying solely on ultraviolet light, heating, or additional oxidants to trigger curing, and reduces the requirements for underwater construction conditions.
[0018] 3. The iron-containing nanoparticle adhesive solution of the present invention can be directly applied to the substrate surface and cured in situ underwater by substrate pressing and end face pressure. It does not require pre-forming or curing in a dry environment and is suitable for underwater bonding, reinforcement, repair and sealing.
[0019] 4. The preparation route of the present invention mainly consists of conventional organic solvent dissolution, Michael addition, precipitation purification and nanoparticle compounding. The process path is relatively short, which facilitates the formation of adhesive solutions that can be coated, sprayed, dipped or immersed, and can adapt to the underwater bonding requirements of different substrate surfaces. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the underwater adhesion mechanism of the iron nanoparticle-controlled hyperbranched adhesive material in this invention. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Reference Figure 1 A method for preparing an underwater in-situ solidified adhesive material based on iron nanoparticle regulation includes the following steps: Hydrophobic amine-terminated polydimethylsiloxane was first dissolved in N,N-dimethylformamide, and then branched multifunctional acrylate, flexible diacrylate, dopamine hydrochloride and benzylamine hydrochloride were dissolved in dimethyl sulfoxide. Finally, the above solutions were mixed together and subjected to a Michael addition reaction at a certain temperature. The resulting solution was poured into methyl tert-butyl ether to precipitate, and the adhesive material was successfully prepared.
[0023] The above adhesive is dissolved in an organic solvent to obtain a universal adhesive solution.
[0024] Iron nanoparticles are mixed into an adhesive solution to prepare an adhesive solution containing iron nanoparticles for coating a substrate surface.
[0025] After applying the above-mentioned adhesive solution containing iron nanoparticles to the substrate surface, the substrate is placed underwater. Another substrate of the same material is then placed on the adhesive layer underwater and pressed for a certain period of time to prepare a sandwich structure. Then, a certain pressure is applied to the joint end face, and the substrate is cured in situ for several days to achieve the bonding between the substrate materials.
[0026] In this invention, hydrophobic branched multifunctional acrylates serve as reactants in the Michael addition reaction and act as branching centers for hyperbranched adhesive materials. The increase in the number of acrylate functional groups is beneficial to the crosslinking density of the adhesive material.
[0027] In this invention, the chain-like amino-terminated polydimethylsiloxane serves as the reactant monomer for the Michael addition reaction. It is a branched chain of hyperbranched adhesive material with strong hydrophobicity and flexibility, and it self-aggregates upon contact with water.
[0028] In this invention, the benzylamine hydrochloride at the end of the branched structure enhances the cohesive energy of the adhesive material through π-π stacking.
[0029] In this invention, dopamine hydrochloride has the ability to penetrate hydration membranes and can enhance interfacial forces with the substrate through hydrogen bonding, π-π stacking, cation-π interactions, and other forces.
[0030] In this invention, the cohesive energy of the polymer is regulated by the coordination bond formed between iron nanoparticles and dopamine-OH in the hyperbranched polymer. When the hyperbranched polymer comes into contact with water, the hydrophobicity of its hydrophobic segments repels water molecules, while simultaneously promoting the self-assembly of the hydrophobic segments and the migration of dopamine hydrochloride to the periphery of the polymer molecular structure, thereby achieving in-situ interfacial bonding between the underwater adhesive and the substrate.
[0031] In this invention, the hydrophobic branched multifunctional acrylate includes one or more of pentaerythritol triacrylate and polydipentaerythritol hexaacrylate.
[0032] In this invention, the diacrylate monomer includes one or more of poly(ethylene glycol) diacrylate, 1,10-bis(acryloyloxy)decane, and di-1,4-butanediol diacrylate.
[0033] In this invention, the temperature of the adhesive polymerization reaction is 70°-90°.
[0034] In this invention, the polymerization reaction of the adhesive is carried out for 4-7 hours.
[0035] In this invention, the organic solvent for dissolving the adhesive comprises one or more of methanol, dimethyl sulfoxide, dichloromethane, acetone, and N,N-methylpropionamide.
[0036] In this invention, the molar ratio of double bonds to amino groups in the adhesive monomer is (1:0.5)-(1.5:0.5).
[0037] In this invention, the mass ratio of the adhesive monomer to dimethyl sulfoxide is (1:1) to (1:3).
[0038] In this invention, the mass ratio of the adhesive to the solvent is (1:0.5):(1:3).
[0039] In this invention, the mass ratio of the iron nanoparticles to the adhesive solution is 0.5% to 2%.
[0040] In this invention, the pressing time is 3-10 minutes.
[0041] In this invention, the curing time is 12-48 hours.
[0042] In this invention, the coating method is not limited to application; methods such as dipping, spraying, or immersion coating to apply the coating slurry to the substrate surface are all within the scope of protection of this invention.
[0043] The following detailed description of the solutions provided by the present invention, in conjunction with the embodiments, should not be construed as limiting the scope of protection of the present invention.
[0044] Example 1 2.6 g of poly(dipentaerythritol) hexaacrylate, 1.3 g of poly(ethylene glycol) diacrylate, 1.8 g of benzylamine hydrochloride, and 25 g of dimethyl sulfoxide were dissolved completely and then added to a side-braced test tube. Triethylamine was added to the side-braced test tube to provide the necessary pH 8 alkaline conditions for the reaction. The reaction mixture was placed in an 80°C oil bath and stirred in the dark for 5 h. After the reaction time was completed, the mixture was washed three times with methyl tert-butyl ether. The purified product was filtered to obtain a high-performance wet adhesive material. The adhesive material was dissolved in methanol and placed in water. Another stainless steel surface was placed on the adhesive layer, and the bonding end face of the substrate was clamped with a medium-sized dovetail clamp. The mixture was cured in situ underwater for 24 h to obtain a stainless steel bonded joint. The bonded joint was subjected to tensile shear tests using a universal testing machine to measure its interfacial adhesion strength.
[0045] Example 2 1.0 g of hydrophobic amine-terminated polydimethylsiloxane was dissolved in 5 g of N,N-dimethylformamide. Then, 2.6 g of polydipentaerythritol hexaacrylate, 1.3 g of poly(ethylene glycol) diacrylate, 1.0 g of amine-terminated polydimethylsiloxane, 3.0 g of dopamine hydrochloride, and 20 g of dimethyl sulfoxide were added to a side-braced test tube. After all monomers were completely dissolved, triethylamine was added to the side-braced test tube to provide the necessary pH 8 alkaline conditions for the reaction. The reaction mixture was placed in an 80°C oil bath and stirred in the dark for 5 h. After the reaction time was completed, the mixture was washed three times with methyl tert-butyl ether. The purified product was filtered to obtain a high-performance wet adhesive material. After dissolving the adhesive material in methanol and incorporating 1% iron nanoparticles, the mixture was coated onto a stainless steel surface. The surface was then placed in water, and another stainless steel surface was placed over the adhesive layer. The joint end faces of the substrate were clamped together with medium-sized dovetail clamps, and the mixture was cured in situ underwater for 24 hours to obtain a stainless steel bonded joint. The bonded joint was subjected to a tensile shear test using a universal testing machine to measure its interfacial adhesion strength.
[0046] Example 3 1.0 g of hydrophobic amine-terminated polydimethylsiloxane was dissolved in 5 g of N,N-dimethylformamide. Then, 2.6 g of polydipentaerythritol hexaacrylate, 1.3 g of poly(ethylene glycol) diacrylate, 2.37 g of dopamine hydrochloride, 0.50 g of benzylamine hydrochloride, and 20 g of dimethyl sulfoxide were added to a side-braced test tube. After all monomers were completely dissolved, triethylamine was added to the side-braced test tube to provide the necessary pH (8) alkaline conditions for the reaction. The reaction mixture was placed in an 80°C oil bath and stirred in the dark for 5 h. After the reaction time was complete, the mixture was washed three times with methyl tert-butyl ether. The purified product was filtered to obtain a high-performance wet adhesive material. After dissolving the adhesive material in methanol and incorporating 3% iron nanoparticles, the mixture was coated onto a stainless steel surface. The surface was then placed in water, and another stainless steel surface was placed over the adhesive layer. The joint end faces of the substrate were clamped together using medium-sized dovetail clamps, and the mixture was cured in situ underwater for 24 hours to obtain a stainless steel bonded joint. The bonded joint was subjected to a tensile shear test using a universal testing machine to measure its interfacial adhesion strength.
[0047] Example 4 1.0 g of hydrophobic amine-terminated polydimethylsiloxane was dissolved in 5 g of N,N-dimethylformamide. Then, 2.6 g of polydipentaerythritol hexaacrylate, 1.3 g of poly(ethylene glycol) diacrylate, 2.37 g of dopamine hydrochloride, 0.50 g of benzylamine hydrochloride, and 25 g of dimethyl sulfoxide were added to a side-braced test tube. After all monomers were completely dissolved, triethylamine was added to the side-braced test tube to provide the necessary pH (8) alkaline conditions for the reaction. The reaction mixture was placed in an 80°C oil bath and stirred in the dark for 5 h. After the reaction time was complete, the mixture was washed three times with methyl tert-butyl ether. The purified product was filtered to obtain a high-performance wet adhesive material. After dissolving the adhesive material in methanol and incorporating 5% iron nanoparticles, the mixture was coated onto a stainless steel surface. The surface was then placed in water, and another stainless steel surface was placed over the adhesive layer. The joint end faces of the substrate were clamped together using medium-sized dovetail clamps, and the mixture was cured in situ underwater for 24 hours to obtain a stainless steel bonded joint. The bonded joint was subjected to a tensile shear test using a universal testing machine to measure its interfacial adhesion strength.
[0048] The adhesive materials prepared in Examples 2, 3, and 4, which were dispersed in water during the curing process in Example 1, had average adhesive strengths of 13 kPa, 626.7 kPa, 696.2 kPa, and 108.3 kPa, respectively, after curing for 24 days. As can be seen from the above embodiments, the preparation method of the bonding material based on iron nanoparticle regulation of the present invention can be directly cured in situ underwater, and the interfacial adhesion strength can reach 696.2 kPa after 24 hours of curing.
[0049] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an underwater in-situ solidification bonding material based on iron nanoparticle regulation, characterized in that, Includes the following steps: Amine-terminated polydimethylsiloxane, branched polyfunctional acrylate, flexible diacrylate, dopamine hydrochloride and benzylamine hydrochloride were mixed in an organic solvent and subjected to Michael addition reaction under alkaline conditions. The reaction product was then precipitated to obtain a hyperbranched adhesive material. The hyperbranched adhesive material is dissolved in an organic solvent to obtain an adhesive solution; Iron nanoparticles are dispersed in the adhesive solution to obtain an adhesive solution containing iron nanoparticles, wherein the iron nanoparticles are used to form coordination with dopamine hydroxyl groups in the hyperbranched adhesive material. An adhesive solution containing iron nanoparticles is applied to the surface of a first substrate to form an adhesive layer. The first substrate is placed underwater, and a second substrate is placed underwater to cover the adhesive layer. Pressure is applied to the joint end face, and underwater in-situ curing is performed to obtain an underwater bonded joint.
2. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The amino-terminated polydimethylsiloxane is first dissolved in N,N-dimethylformamide, and the branched multifunctional acrylate, flexible diacrylate, dopamine hydrochloride and benzylamine hydrochloride are first dissolved in dimethyl sulfoxide. The two solutions are then mixed to carry out the Michael addition reaction.
3. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The branched multifunctional acrylate includes one or more of pentaerythritol triacrylate and polydipentaerythritol hexaacrylate; the flexible diacrylate includes one or more of polyethylene glycol diacrylate, 1,10-bisacryloyloxydecane and 1,4-butanediol diacrylate.
4. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The Michael addition reaction is carried out under alkaline conditions at a temperature of 70°C to 90°C for a time of 4 to 7 hours.
5. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: In the monomers participating in the Michael addition reaction, the molar ratio of double bonds to amino groups is (1:0.5) to (1.5:0.5).
6. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The reaction product was precipitated with methyl tert-butyl ether to obtain the hyperbranched adhesive material; the mass ratio of the hyperbranched adhesive material to the organic solvent used for dissolution was (1:0.5) to (1:3).
7. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The organic solvent in the adhesive solution includes one or more of methanol, dimethyl sulfoxide, dichloromethane, acetone, and N,N-methylpropionamide; the mass of the iron nanoparticles is 0.5% to 2% of the mass of the adhesive solution.
8. The preparation method of an underwater in-situ solidification bonding material based on iron nanoparticle regulation according to claim 1, characterized in that: The adhesive solution containing iron nanoparticles is applied to the surface of the first substrate by coating, dipping, spraying or immersion; after the second substrate covers the adhesive layer, it is pressed for 3 min to 10 min and then cured underwater in situ for 12 h to 48 h under pressure at the joint end face.
9. The application of the underwater in-situ curing adhesive material prepared by the preparation method according to any one of claims 1 to 8 in the bonding, reinforcement, repair or sealing of underwater substrates.
Citation Information
Patent Citations
Palm oil-based underwater adhesive and preparation method thereof
CN113493665A